Improving the Implementation of Accounting, Tax, Online-based Marketing and Sustainability in Savouree Cheesestick Company - Kasim, Erlynda Yuniarti; Martana, Cynthia Riyanti (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2025)
This community service project focuses on improving the implementation of accounting, tax and online marketing to support the sustainability of Cheesestick Savouree's business. The main objective was to improve the orderliness of accounting records, tax reporting and digital optimization of the business to ensure sustainability and better access to financial resources. The methods used included basic accounting and tax training, introduction to accounting software, and strategies to optimize online marketing through the website. The project measured success by the business's ability to maintain accurate financial records, comply with tax regulations, and improve its digital marketing effectiveness. Preliminary results showed that the business demonstrated better financial documentation and digital optimization of the business than before.